PRAKTIK PENIMBANGAN JUAL BELI BUAH SAWIT BERDASARKAN ETIKA BISNIS ISLAM KAMPUNG DOSAN KECAMATAN PUSAKO - Riana, Aidil; Septrimadona, Yessy (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2025)
This study aims to determine the practice of weighing buying and selling of palm fruit based on Islamic business ethics in Dosan Village, Pusako District. This type of research is qualitative research. To obtain the data, the author conducted some steps, there are: interviews, observations, and documentation. The data collection methods used in this research are interviews, observations, library studies and documentation. Data processing and analysis techniques are carried out in three stages, there are: researchers plunge into the field, study, analyze, interpret, and draw conclusions. There are two issues studied in this thesis: (1) How is the practice of weighing the sale and purchase of palm fruit in the Dosan Village, Pusako District, (2) How is the view of the practice of weighing the sale and purchase based on Islamic business ethics. From the results of this study it was found that (1) The practice of buying and selling palm fruit in the Dosan Village is almost the same as other buying and selling, only the method is different. (2) The practice of buying and selling palm fruit is still not in accordance with Islamic business ethics. Because there are still principles of Islamic business ethics that are violated, namely unfairness and uncertainty in the process of weighing palm fruit, and this is prohibited in Islamic law.